Enhancing PT. LVC Website Marketing Strategy To Generate Leads Through Conversion Rate Optimization (CRO) - Haiqa Matahati; Annisa Rahmani Qastharin (Mandalika Institute, 2024)
PT. LVC is a B2B company that provides consultation services for management, QHSE (Quality, Health, Safety, and Environment), regulatory compliance, and business strategy. PT. LVC is aiming to grow its business due to increasing competition. They operate as a consulting firm offering one-time purchase services tailored to each industry. This makes it challenging to secure repeat sales from previous clients. Currently, their primary source of new clients is through their website because after trying other channels, website is the most effective and digital marketing nowadays have proven to be highly impactful. To increase sales and help PT. LVC grow, their website needs to be optimized to generate leads or potential customers, ultimately boosting revenue. Increasing revenue is PT. LVC current primary objective. To achieve this, the conversion rate optimization theory developed by Chris Goward (2012) will be utilized, with a qualitative approach. First, an assessment was conducted to understand the current website marketing strategy through secondary data from company documents. Primary data will then be collected via interviews to identify which elements can be improved through split testing to achieve a higher conversion rate. The interview results were analyzed using thematic analysis, revealing that the aspects to be optimized include adding a free consultation feature, improving the call to action, and designing the